Effects of functional training on physical and technical performance among the athletic population: A systematic review and narrative synthesis - Xiao, W.; Bu, T.; Zhang, J.; Cai, H.; Zhu, W.; Bai, X.; Zhang, L.; Geok, S. K. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The evidence indicates that functional training is beneficial for athletes` physical and technical performance. However, a systematic review of the effects of functional training on athletes` physical and technical performance is lacking. Therefore, this study uses a literature synthesis approach to evaluate the impact of functional training on the physical and technical performance of the athletic population and to extend and deepen the existing body of knowledge.